PENILAIAN RISIKO GEOMEKANIK TAMBANG LOKAL DENGAN METODE ROCK MASS RATING DI LOA JANAN SAMARINDA - Shodiqin, Muhammad Ali; Usop, Tari Budayanti; Susi, Theresia; Hartanto, Singgih; Sutrisno, Herwin; Permana, Indrawan; Perkasa, Petrisly (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
This research explores slope stability at a sandstone mine in Loa Janan Ilir sub-district, Samarinda City, by applying the Rock Mass Rating (RMR) method to identify potential geotechnical risks. The 30-meter Scanline method was used to collect structural data on the bridles, while five key RMR parameters, including uniaxial compressive strength and Rock Quality Designation (RQD), were analyzed to determine the quality of the rock mass. The results revealed that the rock mass at the site has an RMR value of 33.5425, which classifies the slope condition as class IV (poor). This finding highlights the great potential for wedge avalanches to occur, which could threaten the safety of workers and mining operations. As such, this study offers critical insights that can drive decision-making in risk mitigation and safer mine management in the area.